Komunikasi Dialektis Masyarakat Beda Agama di Bojonegoro - Fahrudin, Nanang; Hastjarjo, Sri; Satyawan, Agung (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2018)
This study discusses the manner in which villagers of